Predictive Roles of Some Electrolytes and Biochemical Markers in The Pathophysiology of Renal Failure Diseases; Case-Control Study: Prediksi Peran Beberapa Elektrolit dan Penanda Biokimia dalam Patofisiologi Penyakit Gagal Ginjal; Studi Kasus-Kontrol - Hussein, Mohammed Ali; Hussein, Arwa Alaa; Razzaq, Alaa Siham Abdul; Sobeih, Enas Saad (Indonesian Journal on Health Science and Medicine, 2024)
Objective; detection of the predictive role of some electrolytes and biochemical indicators in the pathophysiology of renal failure diseases. Methods; The present investigation was done in Diyala province within time (July-November 2024). We have 120 blood samples from hemodialysis patients that sleeping in the Ibn-Sina Center for Kidney Dialysis / Ba’aqubah Teaching Hospital. In addition, we collected 80 blood samples from people without diseases (healthy) and depended on them as a control group. Serum levels of all biochemical indicators in all samples of participants were quantified by Cobas e411 machine. SPSS v. 22.0 with Prism v.10 programs were based for the analysis our data. Results; Present outcomes showed that most renal failure patients were males (51.7%) within age groups 41-60 years (48.3%) and living in rural areas (51.7%). Additionally, most patients were no smokers (90.0%) with underweight BMI (33.33%) . Levels of RBS, creatinine, sodium, potassium and urea were highest in patients compared to controls, while the levels of calcium and iron were lowest in patients versus controls with significant difference (p<0.05). ROC curve results showed the urea scored highest sensitivity and specificity (100% and 94%) at cut off (40.50), followed by creatinine (100% and 89%) and albumin (88% and 86%) at cut off values (1.50 and 3.90) respectively, with significant differences (p<0.05), in diagnosis renal failure patients. pearson correlation coefficient showed there is negative significant correlation between RBS and creatinine ( r=-0.189* and p= 0.039), albumin and RBS ( r=-0.310* and p= 0.001), and a positive significant correlation between albumin and sodium (r=-0.227* and p= 0.013) and iron with sodium (r=-0.182* and p= 0.046). Conclusions; We concluded that renal failure disease has more effect on patients >40 years with underweight BMI. No effect of gender, living and smoking on disease. The increase and decreased levels of all indicators are related to kidney damage and loss of homeostasis. Urea, creatinine and albumin indicators are more preferred in screening disease due to have these indicators high sensitivity and specificity than another indicators Highlights: Assessed electrolytes' role in renal failure diagnosis using biochemical indicators. Analyzed 120 hemodialysis patients vs. 80 healthy controls using Cobas e411. Urea, creatinine, albumin showed highest sensitivity/specificity; significant correlations found. Keywords: Renal failure, kidney diseases, renal diseases, electrolytes, biochemical indicators